Prevalence of Vitamin D Deficiency in Thai Women with Uterine Fibroids - Peetinarak, Duangrudee; Sirisuwannatat, Warisa (Thai Journal of Obstetrics and Gynaecology, 2025)
Objectives: To determine the prevalence and associated factors of vitamin D deficiency in Thai women with uterine fibroids. Materials and Methods: A cross-sectional observational study was conducted on 181 Thai women aged 21-49 diagnosed with at least one uterine fibroid with a diameter of 10 mm or greater by ultrasound. The volume of uterine fibroids was calculated using the ellipsoid volume formula. Serum concentrations of 25-hydroxyvitamin D (25(OH)D), parathyroid hormone, and calcium were measured. Then, the participants were stratified into three groups according to their vitamin D status. Results: The prevalence of vitamin D deficiency in Thai women with uterine fibroids was 69.6%. The mean serum concentrations of 25(OH)D, parathyroid hormone, and calcium were 18.8 ± 5.8 ng/ml, 47.9 ± 17.8 pg/ml, and 9.2 ± 0.5 mg/dl, respectively. Neither serum 25(OH)D levels nor serum calcium levels were significantly associated with total uterine fibroid volume (crude mean difference (MD) = -0.01, 95% confidence interval (CI) = -0.02, 0.2, p = 0.949, crude MD = -0.19, 95%CI = -0.48, 0.1, p = 0.193, respectively). However, there was a significant association between serum parathyroid hormone (PTH) levels and total uterine fibroid volume (Adjusted MD = -0.02, 95%CI = -0.06, -0.001, p = 0.006). Conclusion: Although a high prevalence of vitamin D deficiency was observed among Thai women with uterine fibroids, no significant association was found between low serum 25(OH)D levels and the presence of uterine fibroids.